Wall conditioning discharges driven by Т-shaped antenna in Uragan-2M - Lozin, A.V.; Kozulia, M.M.; Korovin, V.B.; Beletskii, A.A.; Glazunov, G.P.; Konotopskiy, A.L.; Baron, D.I.; Moiseenko, V.E.; Grigor’eva, L.I.; Chechkin, V.V.; Shapoval, A.N.; Makhov, M.M.; et al. (Вопросы атомной науки и техники, 2018)
New VHF antenna was introduced at Uragan-2M for VHF vacuum chamber wall conditioning without and with weak magnetic field. It was made as a T-shaped ¼ wavelength double rod. The T-shaped antenna is capable for slow waves generation due to its longitudinal currents. This new wall conditioning tool was studied analyzing vacuum chamber wall conditions and achieved plasma parameters.